Digital Transformation Strategies In The Banking Industry: A Case Study of The Implementation of New Technology at PT. Bank Mandiri (Persero) TBK - Aurellia, Olivia Alvira; Kirana, Laras Puspa; Kaltum, Umi (Jayapangus Press, 2022)
The significant issue in the banking industry today is digital transformation. The changes resulting from digital disruption have transformed how people conduct business and transactions. However, several challenges still need to be addressed in this digital transformation. Therefore, this research aims to analyze the digital transformation process and its impact on the development and growth of PT Bank Mandiri (Persero) Tbk. The research method used is qualitative descriptive with a Systematic Literature Review approach. The data are collected from academic references, books, and reports from official institutions. This research shows that Bank Mandiri has succeeded in implementing a business strategy that is by the five domains of digital transformation, according to Rogers (2016). With this digital transformation, the company has achieved significant business growth.